Teenagers and Young Adults with Cancer: An Exploration of Factors Contributing to Treatment Adherence. (May 2021) - Carr, Elizabeth; Rosengarten, Leah
This systematic appraisal explores the literature surrounding treatment adherence in teenagers and young adults (TYAs) with cancer, with the aim of identifying influential factors that could affect adherence rates. This area is particularly important due to the increased risk of relapse and death associated with nonadherent behavior. In addition, TYAs are found to be the age group least likely to adhere to medical regimes. A comprehensive review of the literature was conducted and seven studies met the inclusion criteria, the articles were then critiqued using a data extraction form and eight themes were generated and discussed. This review highlights the complexities and difficulties in measuring adherence, as well as the key factors affecting adherence, before identifying implications for practice. Good communication and relationships are crucial between all parties involved in TYAs' care including the patients, professionals, parents, and peers. A model of adherence was adapted on the basis of the result of the systematic review, other literature pertaining to adherence in TYAs, and the clinical experience of the authors. Personal factors and external factors, along with treatment factors and interactions with the system all have an effect on the patient's response or ability to adhere. It is apparent that there is a need for more high-quality qualitative and quantitative research in this area, with an emphasis on finding interventions that directly improve adherence specific to this age group.